IMPROVING ELDERLY QUALITY OF LIFE THROUGH ACUPUNCTURE AND SELF-CARE TRAINING IN KOWEL, PAMEKASAN: PENINGKATAN KUALITAS HIDUP LANSIA DENGAN AKUPUNTUR DAN PELATIHAN MANDIRI DI KOWEL, PAMEKASAN - Imandiri, Ario; Hamsidi, Rini; Sumardiko, Dwi Setiani; Latifah, Maasyitoh Sari; Adianti, Myrna; Puruhito, Edith Frederika; Nurrosyidah, Iif Hanifa (Faculty of Vocational Studies, Universitas Airlangga, 2025)
Background: Hypertension is a major public health problem, accounting for approximately 13% of total mortality and causing around 8 million deaths each year. It is highly prevalent among the elderly (aged over 60 years), with rates ranging from 60% to 80%. According to the 2018 Basic Health Research, hypertension cases in Indonesia continue to rise, affecting 63.2% of individuals aged 65–74 years and 69.5% of those aged 75 years and above. Objective: This program aimed to improve the knowledge and skills of elderly individuals in managing hypertension through acupuncture therapy and self-care training. Method: In collaboration with Puskesmas Kowel, the program involved socialization activities, workshops, and a one-month acupuncture therapy service conducted by traditional medicine therapists from Universitas Airlangga. Pre-test and post-test evaluations were administered to assess knowledge improvement and the effectiveness of the therapy in reducing blood pressure. Results: The program successfully enhanced the elderly participants’ understanding of hypertension and acupuncture therapy, as well as their ability to perform self-acupressure techniques. It also strengthened the role of Puskesmas Kowel as an educational and acupuncture therapy center for elderly care in Pamekasan. Conclusion: This initiative provides a foundation for improving the quality of life among the elderly through sustainable complementary therapy practices.